After : nineteen stories of apocalypse and dystopia - Datlow, Ellen; Windling, Terri (Hyperion Books, 2012)
An anthology of nineteen tales by well-known authors of young adult and adult literature which explore the lives of teens raised after a catastrophe, either in the first few years after the change or in the distant future.